2018
DOI: 10.1093/sleep/zsy136
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic mechanisms of obstructive sleep apnea in heart failure patients

Abstract: Heart failure (HF) affects 23 million people worldwide and results in 300000 annual deaths. It is associated with many comorbidities, such as obstructive sleep apnea (OSA), and risk factors for both conditions overlap. Eleven percent of HF patients have OSA and 7.7% of OSA patients have left ventricular ejection fraction <50% with arrhythmias being a significant comorbidity in HF and OSA patients. Forty percent of HF patients develop atrial fibrillation (AF) and 30%-50% of deaths from cardiac causes in HF pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 173 publications
0
19
0
1
Order By: Relevance
“…49 A recent prospective study showed a significant association between BP use and the prevalence of nocturnal AF, the odds ratio of which was even higher in the subset of men with moderate-to-severe sleep disordered breathing (SDB). 50 As SDBs are known to be associated with arrhythmias, 51 this finding may highlight that sufferers of SDB should be prescribed BPs with caution.…”
Section: Bp Use and Af--clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…49 A recent prospective study showed a significant association between BP use and the prevalence of nocturnal AF, the odds ratio of which was even higher in the subset of men with moderate-to-severe sleep disordered breathing (SDB). 50 As SDBs are known to be associated with arrhythmias, 51 this finding may highlight that sufferers of SDB should be prescribed BPs with caution.…”
Section: Bp Use and Af--clinical Studiesmentioning
confidence: 99%
“…Oxidative stress is in turn associated with proarrhythmic changes both at the anatomical level in terms of remodeling 64 and at the level of ion channel and gap junction functional alteration. 51 The latter includes increased late Na + currents, decreased rectifier K + currents, and reduced intercellular connectivity through gap junction connexins. 51 Ultimately, these changes facilitate the development of both arrhythmic triggers and substrates.…”
Section: Fibrosis and Remodelingmentioning
confidence: 99%
“…KNO3(1-3) merupakan suatu senyawa garam yang disusun oleh kation K + dan anion NO3 -. Senyawa (4,5) ini bersifat elektrolit kuat dan merupakan suatu sumber nitrogen paling penting dialam, biasanya kalium nitrar sering disebut sebagai sendawa chili. Karena bersifat elektrolit kuat yang mudah terionisasi menjadi ion-ion, kalium nitrat memiliki kelarutan yang tinggi di dalam air, dengan keadaan 0 0 C dalam 1L air kalim nitrat yang larut dapat mencapai 133g, namun kelarutannya tidak sebesar NaNO3 dengan kondisi yang sama (89,(91)(92).…”
Section: Pendahuluanunclassified
“…Heart failure (HF), often known as congestive HF, occurs when the heart fails to properly pump sufficient blood to the whole body. HF is a major public health concern and is a leading cause of morbidity and mortality worldwide, affecting over 23 million worldwide and resulting in 300,000 annual deaths [1,2]. Accurate and timely diagnosis of HF is essential to ensure appropriate treatment for patients.…”
Section: Introductionmentioning
confidence: 99%